Synthesis of ZnO nanoporous structure materials by two-step thermal oxidation of Zn film. Issue 18 (15th December 2017) - Xu, Qiang; Hong, Rongdun; Chen, Xiaping; Wei, Jiaju; Wu, Zhengyun
Abstract: We describe the synthesis of ZnO nanostructures materials on quartz substrates by a simple two-step thermal oxidation process. Firstly, a thin layer of metallic Zn films are oxidized in nitrogen atmosphere at 350 ℃, and then the samples annealed at high temperature (from 600 to 800 ℃) to improve the crystal quality. The properties of the materials are characterized with X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy and UV–Visible spectroscopy at room temperature. The results show that nano porous structure materials have been formed after the samples annealed at high temperature. Since the small grain size and grain boundary induced effect of conduction band bending, the optical band gap shifts to low energy.